Community Service Strategies through Education and Innovation in Rare Earth Elements Downstreaming - Rusmin Saragih; Imeldawaty Gultom; Elisa Ananda Natalia; Jonathan Parker; Asep Sutarman; Paroli Paroli (ADI Pengabdian Kepada Masyarakat, 2025)
The downstreaming of Rare Earth Elements (REE) in Indonesia has significant potential to support national industrialization but faces challenges in environmental management and community involvement. Communities in REE-producing areas generally lack sufficient understanding of the ecological impacts and economic opportunities related to downstreaming activities. This community service program aims to enhance local community capacity through education and innovation in environmental management and sustainable utilization of REE downstreaming potential. The program applied a qualitative approach through socialization, counseling, group discussions, and community mentoring in potential REE-producing areas. It was supported by policy analysis and participatory observation to assess community understanding and engagement. The community service activities resulted in improved public awareness of environmental impacts and REE waste management. Communities became more active in promoting environmentally friendly practices and initiated simple innovations to support sustainable downstreaming. The conclusion of this community service program shows that education and innovation are effective strategies to strengthen community roles as active partners in supporting sustainable REE downstreaming. This approach can serve as a collaborative model between government, industry, and communities to promote environmentally conscious development of strategic natural resources.